Plastome Evolution of Asyneuma japonicum: Insights into Structural Variation, Genomic Divergence, and Phylogenetic Tree - Byeong-Seon Park; Won-Sub Yoon; Chang-Kug Kim; Yong-Kab Kim (Applied Sciences, 2024)
Asyneuma japonicum is an ornamental flowering plant in East Asia. The genus Asyneuma is difficult to distinguish taxonomically because of its morphological similarities with the genus Campanula. We constructed the first complete plastome of A. japonicum (NCBI accession number: OR805474) using the Illumina platform. This plastome is a circular ring structure with a length of 185,875 base pairs. It is organized into four parts: a pair of inverted repeats (33,084 bp each) as well as large (83,795 bp) and small (35,912 bp) single-copy regions. One hundred nine unique genes were encoded in the assembled plastome. Using structural variations, junction boundaries, rearrangements, divergent hotspots, and phylogenetic analysis, we revealed that A. japonicum was in the closest evolutionary position to Hanabusaya asiatica and it had a large evolutionary divergence from the Campanulaceae family due to gene rearrangements.